Combined effect of high hydrostatic pressure (HHP) and antimicrobial from agro-industrial by-products against S. Typhimurium. (April 2017) - Sanz-Puig, Maria; Moreno, Patricia; Pina-Pérez, M. Consuelo; Rodrigo, Dolores; Martínez, Antonio
Abstract: The inactivation potential of HHP treatment (200 MPa-2 min) was evaluated against Salmonella enterica serovar Typhimurium in cauliflower and mandarin by-product infusions at 37 and 10 °C. By-product infusions exerted a strong antimicrobial effect used alone, achieving 5 log cycles of bacterial reduction for cauliflower by-product infusion after 10 h and for mandarin by-product infusion after 80 h, at 37 °C. The HHP treatment caused only one log cycle of cellular damage, but when inoculated cauliflower or mandarin by-product infusions were subjected to HHP treatment the antimicrobial effect against S. Typhimurium was enhanced, achieving 5 log cycles of inactivation in 6 h at 37 °C in both cases. Inactivation curves were adjusted to the Weibull equation and the kinetic parameters ( b and n ) were obtained. When HHP treatment was combined with by-product infusions, the inactivation rates were greater than when either of the by-product infusions was added separately. In conclusion, a synergistic antimicrobial effect against S. Typhimurium appeared to take place when HHP treatment was combined with cauliflower or mandarin by-product infusion. These infusions could be considered as an additional microbial control measure to guarantee the food safety and food quality of pasteurized food products that are stored under refrigeration. Highlights: The inactivation potential of cauliflower and mandarin by-products was studied. The by-product infusions achieved 5 log cycles of microbial reduction at 37 and 10 °C. The antimicrobial effect of HHP combined with two by-product infusions was evaluated. When two treatments were combined, a synergistic effect was observed. When two treatments were combined, the inactivation rates (Weibull) were greater.